A novel nutritional supplement containing amino acids and chromium decreases postprandial glucose response in a randomized, double-blind, placebo-controlled study - Östman, Elin; Samigullin, Azat; Heyman-Linden, Lovisa; Andersson, Kristina; Björck, Inger; Öste, Rickard; Humpert, Per Magnus (PLOS ONE, 2020)
High postprandial blood glucose levels are associated with increased mortality, cardiovascular events and development of diabetes in the general population. Interventions targeting postprandial glucose have been shown to prevent both cardiovascular events and diabetes. This study evaluates the efficacy and safety of a novel nutritional supplement targeting postprandial glucose excursions in non-diabetic adults. Sixty overweight healthy male and female participants were recruited at two centers and randomized in a double-blind, placebo-controlled, crossover design. The supplement, a water-based drink containing 2.6g of amino acids (L-Leucine, L-Threonine, L-Lysine Monohydrochloride, L-Isoleucine, L-Valine) and 250 mcg of chromium picolinate, was consumed with a standardized carbohydrate-rich meal. The primary endpoint was the incremental area under the curve (iAUC) for venous blood glucose from 0 to 120 minutes. Secondary endpoints included glucose iAUC(0-180 minutes)and the maximum glucose concentration (C-max), for both venous and capillary blood glucose. In the intention-to-treat-analysis (n = 60) the supplement resulted in a decreased venous blood glucose iAUC(0-120min)compared to placebo, mean (SE) of 68.7 (6.6) versus 52.2 (6.8) respectively, a difference of -16.5 mmol/L center dot min (95% CI -3.1 to -30.0,p= 0.017). The C(max)for venous blood glucose for the supplement and placebo were 6.45 (0.12) versus 6.10 (<0.12), respectively, a difference of -0.35 mmol/L (95% CI -0.17 to -0.53,p<0.001). In the per protocol-analysis (n = 48), the supplement resulted in a decreased C(max)compared to placebo from 6.42 (0.14) to 6.12 (0.14), a difference of -0.29 mmol/L (95% CI -0.12 to -0.47,p= 0.002). No significant differences in capillary blood glucose were found, as measured by regular bed-side glucometers. The nutritional supplement drink containing amino acids and chromium improves the postprandial glucose homeostasis in overweight adults without diabetes. Future studies should clarify, whether regular consumption of the supplement improves markers of disease or could play a role in a diet aiming at preventing the development of diabetes.
Gesehen am 18.08.2020